ACTIVITY MODEL OF PLAYING ‘MY HERO IS MY MOTHER’ TO IMPROVE BASIC MOVEMENT SKILLS OF MILD MENTAL RETARDED CHILDREN - Selvi Atesya Kesumawati; Tandiyo Rahayu (Universitas Negeri Medan, 2019)
Fundamental Movement Skills (FMS) of children with intellectual disabilities (ID) had a disruption experience and ID need help from others to develop their potential for movement maximally. The purpose of research and development of FMS through play activities in children with ID was expected to help improve FMS, cognitive abilities, pleasure and focus of attention of children with ID, so that children with ID had valuable experience in their lives, to be able to independently live their daily lives. The research method used was by research and development proposed by Borg and Gall. The subjects of small group trial used 9 children with ID and 4 teachers, and the stages of large group trial used 21 children with ID and 4 teachers in Primary School. The research instrument used rating scale. The data analysis technique was by using Content Validity Ratio (CVR) analysis to prove the validity level of the model of developing FMS through play activities, and used the difference test to prove the effectiveness of increasing the FMS results of children with ID in primary school. The results of the validity test model were high (CVR 0.475), so the mother was a hero game model fit the characteristics of children with ID and effective to increase FMS, cognitive, pleasure and focus of attention.